Prevention of Stunting Through the Use of Local Nutritional Food Ingredients in the Family Food Menu in Nagari Katapiang, Batang Anai District, Padang Pariaman - Mulia, Melindra (Fakultas MIPA Universitas Negeri Padang, 2024)
The prevalence rate of stunting in Nagari Katapiang, Bataang Anai District, Padang Pariaman Regency was still very high very. Therefore, is necessary to handle stunting with counseling and training in making additional processed foods made from local ingredients on the family menu. The purpose of implementing this PKM is to improve the health status of children with stunting in Nagari Katapiang. The PKM method is carried out through socialization, training and demonstrations on making additional food preparations based on local food ingredients. The results of this service activity showed that we have successfully provided education on the importance of children's nutrition, training in making processed food from local ingredients. The results obtained are that family partners are able to identify local ingredients that are full of nutrients and are able to process them into family menus. In addition, the partner communities began to be moved by the importance of health and efforts to deal with stunting in children.